Revolutionizing Healthcare: The Convergence of AR Wearables and AI in Modern Medicine - Sukumar Murali, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of Augmented Reality (AR) wearables with Artificial Intelligence (AI) is revolutionizing modern healthcare delivery, offering innovative solutions to longstanding challenges in patient care. This technical article examines the transformative applications and impacts of these technologies across the healthcare spectrum, from routine patient assessments to complex surgical procedures. By evaluating the implementation of AR-AI systems in clinical workflows, surgical planning, intraoperative guidance, and post-operative care, this study demonstrates significant improvements in healthcare efficiency, diagnostic accuracy, and patient outcomes. The article discusses software infrastructure, providing insights into the future development of these technologies in medical practice.
Keywords: Augmented Reality Healthcare Integration; Medical Artificial Intelligence Systems; Surgical Navigation Technology; Remote Patient Monitoring; Clinical Decision Support Systems